1986
DOI: 10.1016/0014-5793(86)80214-9
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylation of acetone by ethanol‐ and acetone‐inducible cytochrome P‐450 in liver microsomes and reconstituted membranes

Abstract: Acetone oxidation in rat liver microsomes was induced 5-or I-fold by the treatment of the animals with ethanol or acetone, respectively. The apparent K, of the reaction was 0.9 mM, a value lower than the concentration reported for plasma acetone under starvation conditions. The major acetone metabolite was identified as acetol by GC-MS. Acetone oxidation in microsomes was inhibited by typical P-450 inhibitors as well as by compounds (e.g. imidazole) known to interact with the ethanol-inducible P-450 form. Anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 16 publications
0
37
1
Order By: Relevance
“…The first pathway involves an initial hydroxylation of the methyl group of acetone (and probably also butanone) by a cytochrome P450-type monooxygenase to acetol (1-hydroxyacetone) in mammals (11,12). The second known pathway is initiated by an FADH 2 -and NADPH-dependent monooxygenase in a Gordonia sp., which catalyzes a Bayer-Villiger rearrangement to yield methyl acetic ester (methylacetate) as the first intermediate (13).…”
mentioning
confidence: 99%
“…The first pathway involves an initial hydroxylation of the methyl group of acetone (and probably also butanone) by a cytochrome P450-type monooxygenase to acetol (1-hydroxyacetone) in mammals (11,12). The second known pathway is initiated by an FADH 2 -and NADPH-dependent monooxygenase in a Gordonia sp., which catalyzes a Bayer-Villiger rearrangement to yield methyl acetic ester (methylacetate) as the first intermediate (13).…”
mentioning
confidence: 99%
“…Some rats were treated with acetone (5 ml/ kg) intragastrically for two days as described [14]. They received no food, but water ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment of rabbits with acetone, ethanol or imidazole causes the induction of a specific form of liver microsomal cytochrome P-450 which metabolizes aliphatic alcohols [lo -131, acetone [14] and carbon tetrachloride [15]. This form of ethanol-inducible cytochrome P-450 (P-450 LMeb [16], probably identical to isozyme 3a [12]), appears to constitute about 5 -10% of the total cytochrome P-450 in liver microsomes from uninduced animals and 20-40% of the total P-450 in Correspondence to M. Ingelman-Sundberg, Institutionen for Medicinsk Kemi, Karolinska Institutionen, Box 60400, S-10401 Stockholm, Sweden microsomes from induced animals [13, 171.…”
mentioning
confidence: 99%
“…CYP2E1 has a key role in gluconeogenesis as the pathway of formation of lactate or glucose from the ketone body acetone is initiated by CYP2E1, and it has been shown that the pathway contributes 5-10% of gluconeogenetic demands (1,2). The pathway is physiologically relevant as acetone levels are highly elevated in Cyp2E1 null mice compared with wild type, during fasting (3).…”
mentioning
confidence: 99%